Training a support vector machine in R with mlr. (Manning Publications, 2020)
A senior laboratory research scientist at the Francis Crick Institute and Manning's author, Hefin I. Rhys, explains how the SVM algorithm works and teaches you how to train, tune, and cross-validate an SVM model using R Studio and the awesome mlr machine learning package.